2013
DOI: 10.1007/s11250-013-0401-8
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous knowledge on the nutritional quality of urban and peri-urban livestock feed resources in Kampala, Uganda

Abstract: This study identified the indigenous criteria used by livestock farmers in urban and peri-urban areas of Kampala to assess the nutritional quality of available feed resources. Focus group discussions and questionnaire interviews (with a total of 120 livestock farming households) were conducted. The findings showed that banana peels, leftover food and own-mixed feeds were the most commonly used feed resources for cattle, pigs and chickens, respectively. Farmers use several indigenous criteria to judge the nutri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 7 publications
0
21
0
Order By: Relevance
“…In Kampala, the demand for livestock products have increased in recent years due to urbanisation, population growth and increased income (Lumu et al, 2013). However, high quality animal feed protein is expensive and hard to find (Katongole et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In Kampala, the demand for livestock products have increased in recent years due to urbanisation, population growth and increased income (Lumu et al, 2013). However, high quality animal feed protein is expensive and hard to find (Katongole et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these systemic differences, a true merger of knowledge systems is often considerably hampered by the practicalities of life in many places. Lumu, Katongole, Nambi-Kasozi et al (2013) explore the choices in feed made by livestock farmers in and near Kampala, Uganda. In this work, they unearth a vast wealth of indigenous knowledge pertaining to nutrition in various feed sources, and the health impacts feed choices will have on livestock.…”
Section: Knowledge Sovereignty: Threats Adaptation and Mergermentioning
confidence: 99%
“…(Katongole, Nambi-Kasozi, Lumu et al 2012, cited in Lumu et al 2013, 1571. This very real limitation of availability has led to banana peels (widely available from the markets) being reported as the most commonly used source of feed, despite a preference for almost anything else and an awareness 'that the practice compromises nutritional quality' (Lumu et al 2013(Lumu et al , 1577.…”
Section: Knowledge Sovereignty: Threats Adaptation and Mergermentioning
confidence: 99%
“…Even on farms that reported use of banana peels, only a few cows were fed rather than the whole milking herd. Banana plant residues have been reported as important basal and supplementary feed for dairy cows in the tropics (Kimambo and Muya, 1991;Lumu et al, 2013). Previous studies have found that the dry matter digestibility of banana pseudo stems and fruit peelings were 59 and 61%, respectively (Kimambo and Muya, 1991), while crude protein of banana peels was 6% (Nambi-Kasozi et al, 2014), 7.9% (Aregheore and Ikhatua, 1999) and metabolisable energy was 8.7 MJ/kg of dry matter (Aregheore and Ikhatua, 1999).…”
Section: Crop Residues and Agro-industrial By-productsmentioning
confidence: 99%